IMPLEMENTASI METODE KAIZEN TERHADAP KEPUASAN PASIEN DI INSTALASI FARMASI RUMAH SAKIT ROEMANI MUHAMMADIYAH KOTA SEMARANG - Sri Suwarni; Agustina Ratna Wulandari; Ditya Novanda Sari (Jurnal Farmasi & Sains Indonesia, 2019)
Pharmacy service is one of the health services in a hospital that affects the level of patient satisfaction that will affect the quality of the hospital. Kaizen philosophy considers that our way of life such as work life or social life should be focused on continuous improvement efforts. Improvements in kaizen are small and continuous. This study aims to determine the effect of the implementation of the kaizen method in improving the satisfaction of pharmacy services at the Roemani Muhammadiyah Hospital Semarang Pharmacy Pharmacy Installation. This study used an observational design, sampling technique using purposive sampling, data taken in February-April 2019 as many as 240 respondents before implementation and 240 respondents after implementation. Analysis of the data used is the validity test, reliability, DMAIC (define, measure, analyze, improve, and control). The problem solving model in the Kaizen method with 5S is seiri, seiton, seiketsu, seiso, shitsuke. The level of patient satisfaction before the implementation of kaizen was 82.65% with an opportunity for the emergence of patient dissatisfaction at 17.35%. After the implementation of the kaizen there was an increase in patient satisfaction of 89.75% with the opportunity for the emergence of patient dissatisfaction only 10.25%. Chi Square test results p = 0,000 more than 0,005 means that there is a significant difference, so the implementation of the kaizen method affects the increase in satisfaction of pharmaceutical services at the Roemani Muhammadiyah Hospital Semarang Pharmacy Pharmacy Installation.